PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA OPTIK HUMAIRA DI SEKAYU - Syahputra, Dadang; Marsih, Yeni (Universitas muhammadiyah palembang, 2017)
This research entitled “The Influence of Marketing Mix to Consumer Purchase Decision on Optical Humaira Sekayu”. This research is done by using sample as much 80 people taken by purposive sampling. Data collection techniques used are questionnaire and documentation. Answer given by the respondents analyzed quantitatively using SPSS for windows versions 15.0. Research data quality is tested with test validity and realibility that the ordinal scale data is then transformed into a scale interval by using the help method successive intervals are integrated in Microsoft Excel. This research was conducted in the testing primary assumptions the regression includes data normality test, linearity test, multikolinieritas test and heteroskedastisitas test. The research result show the consumer decisions affect the marketing mix. Itcan be seen from the equation of regression result as follows: Y = 11,467 + 0,688X. That is, a good marketing mix will improve consumer decisions. It can be said that the higher the influence of consumer decisions, the higher the marketing mix. Conversely, the lower the marketing mix, the lower the consumer decision.